Analisis Electronic Word of Mouth dan Social Media Marketing Terhadap Purchase Decision yang di Mediasi oleh Purchase Intention (Studi Kasus di Café Habit Kota Sukabumi) - Aurellya Mulyadi, Nazwa (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to determine the influence of Social Media Marketing and Electronic Word of Mouth (eWOM) on Purchase Decision mediated by Purchase Intention among consumers of Cafe Habit Bhayangkara Sukabumi. The background of this study is based on the development of digital marketing trends and changes in consumer behavior influenced by social media and online reviews. The method used is a quantitative approach with Structural Equation Modeling (SEM) analysis techniques based on AMOS 24. Data collection was carried out by distributing questionnaires to 133 respondents who are consumers of Cafe Habit Bhayangkara. The results of the study indicate that eWOM and Social Media Marketing have a positive and significant effect on Purchase Intention. Furthermore, eWOM, Social Media Marketing, and Purchase Intention also have a positive and significant effect on Purchase Decision. These findings indicate that digital marketing strategies, especially those involving social media and online consumer opinions, have an important role in shaping purchase intentions and decisions.